Bioavailability of intranasal drug delivery system - Bhise, Satish Balakrishna; Yadav, Adhikrao Vyankatrao; Avachat, Amelia Makrand; Malayandi, Rajkumar (Asian Journal of Pharmaceutics (AJP), 2014)
Nasal drug delivery system offers lucrative way of drug delivery of both topical and systemic therapies. The high permeability, high vasculature and low enzymatic environment of nasal cavity are well suitable for systemic delivery of drug molecules via nose.The noninvasiveness and self administrative nature of nasal delivery also attracts the formulation scientists to deliver protein and peptide compounds. Despite of all the advantages of nasal drug delivery, the bioavailability of nasally administered products, especially for protein and peptide molecules, is affected by many barriers such as physiological barriers, physicochemical barriers, and formulation barriers. This review will focus on the various bioavailability barriers in nasal drug delivery and the strategies to improve the bioavailability of nasal dosage forms.